A Rare Case of a Lichenoid Rash with Granulomatous Histology - Mahmood, K; Nemazee, L; Innes, N J (International Journal of Pathology, 2018)
Lichen Scrofulosorum, otherwise known as Tuberculid, is a hypersensitivity reaction to mycobacteriumtuberculosis. It is a rarely seen pathology and it presents with a lichenoid rash and a granulomatouspicture is seen on histology.We present the case of a 72 year old man with a background of pleural and renal Tuberculosis, whopresented with a 10 month history of lichenoid papules, widespread over the trunk and limbs. Skin biopsyshowed granulomatous inflammation. This clinical picture and histology, together with a backgroundof tuberculosis in the past, was highly suggestive of Lichen Scrofulosorum.Although tuberculid occurs rarely, it may be the only marker of occult TB and which may not be discoveredotherwise. Therefore it is important that skin physicians are able to detect and diagnose tuberculidand so treat accordingly.